(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In this article, the training of qualified young specialists with knowledge and skills in the rational use of energy-saving resources of industrial technologies plays an important role in solving the above urgent task. In particular, local manufacturers and foreign enterprises are involved in the development and installation of coal-fired boilers, this information is detailed in the article.